Humanist-Quranic Based Managerial Organizational Culture in Indonesia: Ethnographic Study - Muntaqo, Rifqi; Muntaqo, Lutfan; El Syam, Robingun Suyud; Wan Jusoh, Wan Noor Hazlina (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze the managerial and organizational culture in one of the Islamic universities in Indonesia that has humanist and Qur’anic characteristics, as well as the forms of its implementation. This is expected to be a differentiator from the organizational culture patterns in other higher education institutions, especially private ones. This study uses an ethnographic approach with a data collection flow that adopts the Spradley model. This method was chosen to understand in depth how the integration of humanist and Qur’anic values is applied in the managerial culture that is characteristic of the university. Data collection was carried out through participatory observation, unstructured interviews, and closed questionnaires. Qualitative data validation used triangulation techniques of sources, methods, and researchers. Data analysis techniques were carried out qualitatively using the Miles and Huberman model. The results of the study indicate that the managerial culture applied in the Islamic university has unique characteristics, namely integrating the values contained in the Qur’an, which are manifested in real humanistic actions. This can be seen both in terms of regulations and interactions within it involving the leadership, lecturers, and employees. In addition, this study also found how the institution collaborates with external partner institutions.